Kreatywność zasobów ludzkich w świetle badań empirycznych mieszkańców obszarów wiejskich - Pluta, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The success contemporary organization is depend on creativity human resource. The paper describes results of the research on the subject of creativity of rural area inhabitants. The author tries to find an answer for following question: Are the inhabitants of rural areas creative? (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 374-382